Transmembrane serine protease 2 Polymorphisms and Susceptibility to Severe Acute Respiratory Syndrome Coronavirus Type 2 Infection: A German Case-Control Study - Schönfelder, Kristina; Breuckmann, Katharina; Elsner, Carina; Dittmer, Ulf; Fistera, David; Herbstreit, Frank; Risse, Joachim; Schmidt, Karsten; Sutharsan, Sivagurunathan; Taube, Christian; Jöckel, Karl-Heinz; Siffert, Winfried; et al. (Frontiers in Genetics, 2021)
The transmembrane serine protease 2 (TMPRSS2) is the major host protease that enables entry of the severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) into host cells by spike (S) protein priming. Single nucleotide polymorphisms (SNPs) in the gene TMPRSS2 have been associated with susceptibility to and severity of H1N1 or H1N9 influenza A virus infections. Functional variants may influence SARS-CoV-2 infection risk and severity of Coronavirus disease 2019 (COVID-19) as well. Therefore, we analyzed the role of SNPs in the gene TMPRSS2 in a German case-control study. We performed genotyping of the SNPs rs2070788, rs383510 and rs12329760 in the gene TMPRSS2 in 239 SARS-CoV-2-positive and 253 SARS-CoV-2-negative patients. We analyzed the association of the SNPs with susceptibility to SARS-CoV-2 infection and severity of COVID-19. SARS-CoV-2-positive and SARS-CoV-2-negative patients did not differ regarding their demographics. The CC genotype of TMPRSS2 rs383510 was associated with a 1.73-fold increased SARS-CoV-2 infection risk, but was not correlated to severity of COVID-19. Neither TMPRSS2 rs2070788 nor rs12329760 polymorphisms were related to SARS-CoV-2 infection risk or severity of COVID-19. In a multivariable analysis the rs383510 CC genotype remained an independent predictor for a 2-fold increased SARS-CoV-2 infection risk. In summary, our report appears to be the first showing that the intron variant rs383510 in the gene TMPRSS2 is associated with an increased risk to SARS-CoV-2 infection in a German cohort.